Ekosistem Belajar Digital Sekolah: Studi tentang Interaksi Teknologi, Guru, dan Siswa - Ahmad Zulkarnain Wahid; Siti Raihana Oktaria; Muhammad Farhan Basuki (PT. Panca Publishing Indonesia, 2026)
The development of digital technology has transformed the school learning environment into a complex digital ecosystem. This study examines interaction patterns between technology, teachers, and students within the digital learning ecosystem in secondary schools in South Sumatra Province. Using a qualitative approach with a multiple case study design, the research was conducted in six schools across three regencies over a period of ten months. Data were collected through classroom observations, interviews with 24 teachers and 48 students, focus group discussions, and document analysis. The findings reveal four dominant interaction patterns: technologically mediated pedagogical dynamics, adaptation of teachers' roles, development of students' digital agency, and sustainability of the institutional ecosystem. Schools with mature digital ecosystems demonstrate seamless technology integration, strong professional learning communities, and transformational leadership. The study concludes that the effectiveness of the digital learning ecosystem is determined by the quality of human interactions and the institutional support structures that enable meaningful, equitable, and sustainable learning experiences